Ultrasound-mediated nanomaterials for the treatment of inflammatory diseases - Kai Zhang; Tingting Wang; Xingyong Huang; Peng Wu; Lufan Shen; Yuanyuan Yang; Wenyu Wan; Siyu Sun; Zhan Zhang (Ultrasonics Sonochemistry)
Sterile and infection-associated inflammatory diseases are becoming increasingly prevalent worldwide. Conventional drug therapies often entail significant drawbacks, such as the risk of drug overdose, the development of drug resistance in pathogens, and systemic adverse reactions, all of which can undermine the effectiveness of treatments for these conditions. Nanomaterials (NMs) have emerged as a promising tool in the treatment of inflammatory diseases due to their precise targeting capabilities, tunable characteristics, and responsiveness to external stimuli. Ultrasound (US), a non-invasive and effective treatment method, has been explored in combination with NMs to achieve enhanced therapeutic outcomes. This review provides a comprehensive overview of the recent advances in the use of US-mediated NMs for treating inflammatory diseases. A comprehensive introduction to the application and classification of US was first presented, emphasizing the advantages of US-mediated NMs and the mechanisms through which US and NMs interact to enhance anti-inflammatory therapy. Subsequently, specific applications of US-mediated NMs in sterile and infection-associated inflammation were summarized. Finally, the challenges and prospects of US-mediated NMs in clinical translation were discussed, along with an outline of future research directions. This review aims to provide insights to guide the development and improvement of US-mediated NMs for more effective therapeutic interventions in inflammatory diseases.